P34 Are nursing staff sufficiently educated and competent in managing patients with a chest drain?. (2nd December 2011) - Fremlin, G; Baker, R; Walters, G; Fletcher, T
Abstract : Background: The British Thoracic Society recommends that patients with chest drains should be nursed on a ward familiar with their care. Instruction from doctors and appropriate training of nursing staff is imperative to minimise complications associated with chest drains. Our audit aimed to determine the nurses' level of knowledge regarding chest drain management and the support and direction provided by doctors following drain insertion. Methods: We undertook a prospective case-note audit of chest drain insertion, management and complication rates. In addition we interviewed 100 nurses across medical wards familiar with chest drains, and they undertook a structured questionnaire about training, knowledge and confidence in chest drain care. Results: 29 chest drains were inserted. 65% patients suffered no complications but 25% patients reported pain during or following drain insertion. Potential for serious incidents was high; 20% of effusions drained >2 l within the first hour and 10% of pneumothoraces were clamped following insertion. Although all nurses reported to have managed a drain only 12% had received formal training and only 34% felt confident in managing a drain. Complication rates correlated with nurses' responses; 34% believed pain-relief was only indicated following insertion; 8% would clamp a drain inserted for a pneumothorax, while 20% were unsure whether a pneumothorax drain should be clamped; 16% believed pleural effusion drains should never be clamped, while 28% were unsure. Of those who believed an effusion drain should be clamped, 29% felt this was indicated after >2 l was drained within the first hour. Of concern, nurses on respiratory wards appeared to have limited knowledge of drain management. 78% of nurses felt poor instruction was provided by ward doctors with regard to chest drain management. Conclusions: Lack of evidence-based nursing care and insufficient training has resulted in uncertainty and knowledge deficit in important aspects of chest drain care, exposing patients to avoidable complications. Poor instructions to nurses from doctors following drain insertion further compromises patient care. A carefully designed and implemented care bundle to guide nurses through drain management could significantly lower post-insertion complications; an example has been rolled out and is illustrated.